Novel Cost-Efficient Graphene-Based Impedance Biosensor for the Analysis of Viral Cytopathogenicity and the Effect of Antiviral Drugs - Schultz, Anke; Knoll, Thorsten; Urban, Andreas; Schuck, Herbert; von Briesen, Hagen; Germann, Anja; Velten, Thomas (Frontiers in Bioengineering and Biotechnology, 2021)
Biosensors become increasingly relevant for medical diagnostics, pharmaceutical industry and environmental technology, for example, to test new drugs easily and reliably or to detect cell growth in changing environmental conditions. Novel materials like graphene are promising candidates to produce biosensors on an industrial scale by means of printing processes. To reach this aim, methods for the reliable and automated production of electrode structures and their coating are required. We present an impedance biosensor in the format of a microtiter plate, fabricated by highly efficient roll-to-roll printing of graphene-based microstructures on large-area polymer foils. Evidence of the suitability of the printed graphene biosensors was shown for impedance-based monitoring of viral cytopathogenicity and its inhibition in the presence of antiviral drugs. The developed system is a promising approach towards cost-efficient impedimetric biosensors for high-throughput screening in vaccine research and antiviral drug development.